The Development of Bioindustry Technology in Realizing IoT-Based Sustainable Agricultural Industry Waste Management in West Java - Evelyn, Grace; Saputra, Aditya Vieri; Anggadewi, Dinda Damarisa; Amrina, Uly (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The threat of climate change is increasing, especially the damage to nature caused by pollution in the agricultural sector. The impact of agricultural waste that is not managed optimally can reduce ecosystem function and disrupt food security stability. This research/research aims to mapping, analyzing, and developing Internet of Things (IoT)-based bioindustry technology in order to create an efficient, green and sustainable agricultural industry. This research uses quantitative methods with agroecology theory related to the development of agricultural waste management systems. The benefits of anaerobically processing agricultural waste such as in the West Java region is to create an optimal, efficient and land-saving food production system. Biotechnology based on the IoT automation system is a technology that can control agricultural food production waste by composting waste into new product that can be used. Therefore, we conducted research on agricultural waste, namely husk waste and cow blood water from slaughterhouses. The end result of the waste treatment is Bokashi Fertilizer and Liquid Organic Fertilizer by using biotechnology technology.